American Accounting Association Committee on International Accounting Research 1967 Report International Financial Reporting And The AAA Basic Standards. - Berg, Kenneth B.; Estes, Ralph W.; Ramanauskas, Helene M. A.; Savoie, Leonard M.; Mueller, Gerhard G. (The Accounting Review, 1968)
This article highlights the report of the Committee on International Accounting Research of the American Accounting Association. The report is the result of the 1966/67 research effort of the Committee on International Accounting Research of the American Accounting Association. In carrying out its assignment the Committee felt that it would be appropriate to comment on the usefulness of the "standards" and "guidelines" contained in "A Statement of Basic Accounting Theory" as well as to appraise selected international accounting reports in the light of these standards and guidelines. For this purpose the committee decided to study a recent annual report for each of five companies from each of the following countries: Argentina; Japan; The Netherlands; Sweden; and Great Britain. While the companies included in the study collectively do a significant amount of international business, it is felt that the sample was too restricted to justify generally valid observations. The comments in this report are therefore best viewed as tentative conclusions which should be tested by more comprehensive studies before being accepted.